“This Period of Desperate Enterprise”: British efforts to secure Kingston from rebellion in the winter of 1837-1838 - Garcia, Robert (Ontario History, 2009)
This article looks at the reaction of the British military authorities in Kingston to the outbreak of the Upper Canada Rebellion in December 1837. The revolt had come at an awkward time. The vast majority of Kingston’s regular garrison had been earlier dispatched to quell the uprising in Lower Canada leaving the town open to Patriot attack. As well, Fort Henry, whose construction had begun in 1832 and the lynch pin of a proposed system of fortifications designed to protect the province’s chief military depot, Royal Navy dockyard and the entrance to the Rideau Canal, was not yet complete. Lead by Richard Bonnycastle of the Royal Engineers, a small cadre of British regulars and retired veterans took vigorous steps to organize and train the eager but raw Canadian militia and volunteers. The effectiveness of the training was realized in late February 1838 when the Patriots made their major attempt to capture Kingston.